Acrobatics of the posthumous. Unpublished rewrites by Silvina Ocampo (Anclajes, 2023)
The first edition of Silvina Ocampo’s 1937 book, Viaje Olvidado, includes several handwritten, unpublished rewritings. Following our hypothesis, rather than corrections that restore meanings and certainties, they constitute a retraction, an intensified “return” to indeterminacy and ambiguity that characterizes the stories in the volume. To demonstrate this, we will analyze the author’s rewriting of four paradigmatic stories: “Cielo de claraboyas”, “La calle Sarandí”, “El retrato mal hecho” and “Los funámbulos”.
Keywords: Silvina Ocampo; Argentine literature; Literary criticism; Twentieth century; Argentina